Ecological footprint and investment in natural capital in Asia and the Pacific. (WWF report., 2012)
Despite the rich natural capital in the Asia and Pacific region, this report reveals that biodiversity is in decline in all types of ecosystems, including in forests, rivers and oceans, with the rate of species loss about twice the global average.